Exposure to traffic-related particle matter and effects on lung function and potential interactions in a cross-sectional analysis of a cohort study in west Sweden. Issue 10 (19th October 2020) - Carlsen, Hanne Krage; Nyberg, Fredrik; Torén, Kjell; Segersson, David; Olin, Anna-Carin
Abstract : Objectives: To investigate the long-term effects of source-specific particle matter (PM) on lung function, effects of Surfactant Protein A (SP-A) and glutathione S-transferase (GST) genes GSTP1 and GSTT1 gene variants and effect modification by single-nucleotide polymorphism (SNP) genotype. Design: Cohort study with address-based annual PM exposure assigned from annual estimates of size (PM10, PM2.5 and PMBC ) and source-specific (traffic, industry, marine traffic and wood burning) dispersion modelling. Setting: Gothenburg, Sweden. Participants: The ADult-Onset asthma and NItric oXide Study had 6685 participants recruited from the general population, of which 5216 (78%) were included in the current study with information on all variables of interest. Mean age at the time of enrolment was 51.4 years (range 24–76) and 2427 (46.5%) were men. Primary and secondary outcome measures: The primary outcome was forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV1 ). Secondary outcome measures were effects and gene–environment interactions of SP-A and GSTT1 and GSTP1 genotypes. Results: Exposure to traffic-related PM10 and PM2.5 was associated with decreases in percent-predicted (% predicted) FEV1 by −0.48% (95% CI −0.89% to −0.07%) and −0.47% (95% CI −0.88% to −0.07%) per IQR 3.05 and 2.47 µg/m 3, respectively, and with decreases in % predicted FVC by −0.46% (95% CI −0.83% to −0.08%) and −0.47% (95% CI −0.83% to −0.10%). Total and traffic-related PMBC was strongly associated with both FEV1 and FVC by −0.53 (95% CI −0.94 to −0.13%) and −0.43% (95% CI −0.77 to −0.09%) per IQR, respectively, for FVC, and similarly for FEV1 . Minor allele carrier status for two GSTP1 SNPs and the GSTT1 null genotype were associated with decreases in % predicted lung function. Three SP-A SNPs showed effect modification with exposure to PM2.5 from industry and marine traffic. Conclusions: PM exposure, specifically traffic related, was associated with FVC and FEV1 reductions and not modified by genotype. Genetic effect modification was suggested for industry and marine traffic PM2.5 .